Efektivitas Senam Dismenorea dan Yoga dalam Mengurangi Nyeri saat Menstruasi - anisa wigati rozifa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Adolescence is marked by changes in body development associated with puberty. In adolescence, women experience ovulation and menstruation, sometimes accompanied by menstrual pain (dysmenorrhea). Women have experienced dysmenorrhea as much as 90%. Some efforts to reduce dysmenorrhea and use drugs can use complementary therapies, namely yoga exercise therapy and dysmenorrhea exercise. Yoga and gymnastics dysmenorrhea is one of the non-pharmacological techniques to treat menstrual pain that provides a distraction effect so that it can reduce abdominal cramps. This condition is exacerbated by unstable psychological conditions, such as stress, depression, excessive anxiety, and excessive sadness or joy. This study aimed to determine how effective yoga and dysmenorrhea reduce pain during menstruation (dysmenorrhea).Methods: This research method is Quasi Experiment Design with pre-and post-test designs. In this design, there are two experimental groups. This research was conducted from October – December 2021. Using a random sampling method, the research sample was 35 respondents for each group. Data collection techniques with pain scale observation sheets using a number scale with a score of 1-10 with criteria for mild pain, moderate pain, and severe pain. The data analysis used is an independent samples test.Results: Characteristics of respondents in this study include: the majority of respondents aged 17-19 years, class XI as many as 42 respondents, First Day of Last Menstrual Period (LMP) 11-20. The results of the Chi-square test analysis obtained x² count 4.983 > x² table 3.841.Conclusion: This shows that yoga more effectively reduces menstrual pain (dysmenorrhea) in adolescent girls adolescent than in dysmenorrhea gymnastics girls in the working area of the Jagir Health Center.